Inclusive Scaling Pathways: Insights from AICCRA’s work on climate-smart agriculture and climate information services - Ewell, Hanna Louise Deborah; Huyer, Sophia; Gondwe, Therese; Girvetz, Evan Hartunian (2025)
Scaling is not gender neutral: Social differences such as gender, age, and class shape who benefits; inclusive pathways are needed to avoid reinforcing inequalities. Participation drives impact: Co-design and active involvement of marginalized groups improve adoption, equity, and resilience. Inclusivity boosts scalability: Tailored approaches enhance relevance and sustainability, making impact at scale more effective